A psychophysical study comparing massage to conditioned pain modulation: A single blind randomized controlled trial in healthy participants. (July 2021) - Wilson, Abigail T.; Riley, Joseph L.; Bishop, Mark D.; Beneciuk, Jason M.; Godza, Mutsa; Cruz-Almeida, Yenisel; Bialosky, Joel E.
Abstract: Introduction: Pain-inducing massage results in greater pain inhibition than pain free massage, suggesting a mechanism dependent on conditioned pain modulation (CPM). The purpose of this study was to test the hypothesis that pain inducing massage produces similar magnitude of reduction in pain sensitivity as a cold pressor task and that baseline conditioned pain modulation efficiency predicts pain inducing massage related hypoalgesia. Methods: Sixty healthy participants were randomly assigned to receive either pain inducing massage to the neck, cold pressor task to the hand, or pain free massage to the neck. Participants also underwent pre and immediate post-intervention quantitative sensory testing. A repeated measures ANCOVA determined between group differences in pain sensitivity changes. Results: Pain inducing massage used as a conditioning stimulus resulted in comparable experimental pain sensitivity changes as a cold pressor task (p > 0.05). Pain intensity during the intervention demonstrated a weak correlation (r = 0.20, p = 0.12) with changes in pain sensitivity at a remote site. Individuals with an efficient CPM at baseline who received the pain inducing massage displayed greater increases in pressure pain threshold compared to individuals with a less efficient CPM indicating the potential benefit of treatment stratification by mechanism. Conclusion: Although pain inducing massage resulted in less self-reported pain than a cold pressor task, both resulted in similar magnitude of the CPM response, suggesting shared underlying mechanisms. Understanding mechanisms of interventions can move us closer to mechanistic based treatments for pain which is consistent with a personalized medicine approach to care.